Predictors of in-hospital mortality in primary intracerebral haemorrhage in rural Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; How, Soon Hin; Abdul Rashid, Mohd Amran; Che Abdullah, Shahrin Tarmizi; Omar, Ahmad Marzuki; Shah, Anis (Asia Pacific Stroke Conference, 2011)
Introduction: Primary intracerebral hemorrhage (PICH) remains the deadliest and most disabling form of stroke. Despite that, there is paucity of epidemiological data on this condition in Malaysia. The aim of our study was to analyse the frequency of various risk factors among our PICH patients and determine the predictors of in-hospital mortality. Methods: A prospective study conducted among PICH patients at a tertiary care level hospital. Results: A total of 160 (93 male and 67 female) eligible patients with age range from 25 to 85 years (mean age 58.30 ± 11.44 years) were evaluated. Hypertension was the commonest risk factor (74.4%), followed by diabetes mellitus (18.8%) and cigarette smoking (36.3%). The commonest localization of ICH was lobar (43.8%) followed by basal ganglia / thalamus (28.1 %) and multilobar (13.1%). The overall mortality was 32.5 %. About one third (32.7%) of the deaths occurred within first 24 hours, this rose to 38.5% within first 2 days and 84.6% within one week. The significant independent predictors of acute in- hospital mortality were posterior fossa bleed (OR 11.01; 95% CI 3.21 to 37.81), hematoma volume >60ml (OR 4.72; 95% CI 1.34 to 16.64), mid line shift (OR 3.32; 95% CI 1.05 to 10.50) and intraventricular extension of haemorrhage (OR 5.69; 95% CI 2.24 to 14.47). Conclusion: PICH is associated with high mortality. The characteristics of hematoma and its localization was the most important factor to determine in-hospital mortality. Keywords: Primary intracerebral haemorrhage